2014
DOI: 10.1037/ppm0000024
|View full text |Cite
|
Sign up to set email alerts
|

More than a dalliance? Pornography consumption and extramarital sex attitudes among married U.S. adults.

Abstract: Extramarital sex is one of the most commonly cited reasons for divorce. U.S. adults who have more positive extramarital sex attitudes are more likely to engage in extramarital sex. Given pornography's positive portrayal of extramarital sex, several recent studies have explored whether people who consume pornography have a more positive attitude toward extramarital sex. Consistent correlations have been found, but limitations to inference are posed by the sampling of adolescents and college students and the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…In the married subsample of this panel study, it was found that pornography consumption was related to more positive subsequent extramarital sex attitudes, but, again, extramarital sex attitudes did not predict subsequent pornography consumption (Wright, Tokunaga, & Bae, 2014). Finally, among Dutch adolescents in grades 8-10, boys who had more permissive sexual attitudes at the beginning of the study showed a stronger increase in their sexually explicit internet material (Doornwaard, van den Eijnden, Overbeek, & ter Bogt, 2014) but no such link was found for girls.…”
mentioning
confidence: 83%
“…In the married subsample of this panel study, it was found that pornography consumption was related to more positive subsequent extramarital sex attitudes, but, again, extramarital sex attitudes did not predict subsequent pornography consumption (Wright, Tokunaga, & Bae, 2014). Finally, among Dutch adolescents in grades 8-10, boys who had more permissive sexual attitudes at the beginning of the study showed a stronger increase in their sexually explicit internet material (Doornwaard, van den Eijnden, Overbeek, & ter Bogt, 2014) but no such link was found for girls.…”
mentioning
confidence: 83%
“…EmmersSommer, Hertlein, & Kennedy, 2013;Lambert, Negash, Stillman, Olmstead, & Fincham, 2012;Maddox et al, 2011;Wright, Tokunaga, & Bae, 2014) and sexist and sexually aggressive attitudes (Hald & Malamuth, 2015;Hald, Malamuth, & Lange, 2013) and has investigated the role of SEM use in couples' relationship satisfaction primarily as a side effect.…”
Section: Introductionmentioning
confidence: 97%
“…First, viewing pornography at all predicts lower levels of marital quality over time and this relation is not significantly moderated by whether married Americans are violating their moral views by using it. This would suggest that the primary issue is not whether pornography users are experiencing moral incongruence thereby negatively affecting their marriage, but the other factors that are attendant to pornography use that could include negatively influencing viewers' sexual scripts (Sun et al, ; Wright et al, ; Zillmann & Bryant, ) or creating tension in the relationship around one partner's private pornography use (Maddox et al, ; Willoughby et al, ). And yet, moral incongruence plays a role in intensifying the negative association between pornography use and marital quality for those who already view pornography.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if this hypothesis does not hold true, it would suggest that the connection between pornography use and marital quality stems primarily from other factors described in the literature outlining scripting and viewing discrepancy theories (Perry, ; Sun et al, ; Willoughby et al, ; Wright et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation